POTENSI PENGELOLAAN AREN DI DESA KALOBBA KECAMATAN TELLU LIMPOE KABUPATEN SINJAI - Nikmah, A. Khaeril; Dassir, Muhammad; Gautama, Iswara (Jurnal Riset Multidisiplin Agrisosco, 2023)
Aren is one type of palm plant that is almost spread throughout Indonesia. The importance of this research is as the main source of information in supporting the data collection of NTFP potential, especially the distribution of aren palm in Kalobba Village, Tellu Limpoe District, Sinjai Regency. This research was conducted in March-April 2023, in Kalobba Village, Tellu Limpoe District, Sinjai Regency, South Sulawesi Province. Data collection was carried out by determining the location of the observed plant area using systematic sampling with random method. Making plots with a plot size of 20 m x 20 m. then conduct interviews with palm farmers and analyze the data from the interviews. The potential of palm sugar in Kalobba Village, Tellu Limpoe Subdistrict, Sinjai Regency has an average land area of 0.2 ha or 20 are with the number of palm trees in 5 plots of 19 trees. The number of palm trees that can be tapped is 6 trees while the number of palm trees that cannot be tapped is 13 trees. The 6 tapped palm trees produce 10-30 liters per day. While other aren palm potential such as fruit and leaves are still rarely utilized.